Development of LKPD Based on Teaching at the Right Level to Improve the Critical Thinking Ability of Grade XI Students - Rozalia, Rozalia; Purwanto, Andik; Hamdani, Dedy (Kasuari: Physics Education Journal (KPEJ), 2024)
This study aims to determine the feasibility, improvement of critical thinking skills, and student responses to LKPD based on Teaching at the Right Level. The Research and Development method, namely the ADDIE model, is used in this study. The distribution of the needs questionnaire at the analysis stage with a percentage result of 78% means that grade XI students of SMAN 8 Bengkulu city need LKPD TaRL teaching materials with the category of agreeing. The planning stage is carried out by designing a TaRL-based LKPD. The development stage was carried out to make LKPD, then validated by three experts consisting of two lecturers and one teacher, a percentage of 91% was obtained which was considered very feasible. At the implementation stage, a pretest was carried out before learning using LKPD TaRL in grade XI 2 SMAN 8 Bengkulu city, then a postest with an increase in N-gain of 0.78 was categorized as high and a student response of 88% in the very good category. The evaluation stage is carried out at each stage of the ADDIE model. It was found that the development of TaRL-based LKPD was very feasible, the student response was very good, and the increase in N-gain was high.